Автоматизированная система контроля механических нагрузок энергетического оборудования - Горкунов, Борис Митрофанович; Львов, Сергей Геннадьевич; Горкунова, Ирина Борисовна (НТУ "ХПИ", 2013)
The effective algorithms of eddy-current microprocessor devices, that implement the multyparameters control methods of electromagnetic and geometric charecteristics of ferromagnetic and non-magnetic products are developed. A functional diagram of an automatic complex for multiparameter eddy current testing, implemented using a high-precision measuring equipment are proposed.
Keywords: микропроцессорные устройства; вихретоковой неразрушающий контроль; цилиндрические изделия; физико-механические воздействия; высокоточная измерительная аппаратура; автоматизированный комплекс контроля